Synchronous subnanosecond clock and data recovery for optically switched data centres using clock phase caching - Kari A. Clark; Cletheroe, Daniel; Gerard, Thomas; Haller, Istvan; Jozwik, Krzysztof; Shi, Kai; Thomsen, Benn; Williams, Hugh; Zervas, Georgios; Ballani, Hitesh; Bayvel, Polina; Costa, Paolo; et al. (Nature Electronics, 2020)
The rapid growth in the amount of data being transferred within data centres, combined with the slowdown in Moore’s Law, creates challenges for the future scalability of electronically switched data-centre networks. Optical switches could offer a future-proof alternative, and photonic integration platforms have been demonstrated with nanosecond-scale optical switching times. End-to-end switching time is, however, currently limited by the clock and data recovery time, which typically takes microseconds, removing the benefits of nanosecond optical switching. Here we show that a clock phase caching technique can provide clock and data recovery times of under 625 ps (16 symbols at 25.6 Gb s−1). Our approach uses the measurement and storage of clock phase values in a synchronized network to simplify clock and data recovery versus conventional asynchronous approaches. We demonstrate the capabilities of our technique using a real-time prototype with commercial transceivers and validate its resilience against temperature variation and clock jitter.